Systemic therapy strategies for elderly patients with gastric cancer - Yukiya Narita; Kei Muro (Therapeutic Advances in Medical Oncology)
Gastric cancer (GC) is the fifth most common malignancy and a leading cause of cancer mortality globally, with particularly high rates in East Asia. The median age at diagnosis is approximately 68 years, and over half of the cases occur in patients aged >65 years. As the life expectancy increases, the proportion of elderly patients with GC increasing, and this population presents unique treatment challenges. Conventional chemotherapy regimens were developed primarily for younger populations and may not be optimal for older adults due to age-related declines in organ function, comorbidities, and differing treatment preferences. The present review discusses the epidemiologic treatment trends among elderly GC patients, the limitations of defining “elderly” solely by chronological age, and the importance of comprehensive geriatric assessments, including the G8 screening tool, for guiding therapy. Evidence indicates that doublet chemotherapy combinations—such as S-1 plus oxaliplatin or capecitabine plus oxaliplatin—benefit fit elderly patients, whereas frailer individuals may be better suited for monotherapy (e.g., S-1 or capecitabine alone) or de-intensified regimens. Although immune checkpoint inhibitors and targeted agents, such as zolbetuximab, are now used in clinical practice, evidence from clinical trials specific to elderly patients remains severely limited. In addition, microsatellite instability-high tumors, more common in older patients, show exceptional responses to immune checkpoint inhibitors, suggesting a potential for chemotherapy-free regimens. This review highlights the importance of personalized, geriatric-guided treatment strategies and discusses pivotal clinical trials involving elderly GC patients. Future research should focus on optimizing regimens and integrating targeted therapies to improve outcomes while minimizing toxicity in this growing population. This review focuses primarily on treatment strategies for elderly patients with advanced or metastatic GC, where systemic therapy decisions must balance efficacy with age-related vulnerabilities.